XVII Shishkin Readings: “Elites and Morality” (to the Memory of Gennady Ashin) - O. V. Gaman-Golutvina; V. S. Glagolev; K. M. Dolgov; S. A. Kravchenko; E. V. Ochotskiy; A. N. Samarin; A. V. Shestopal (Vestnik MGIMO-Universiteta)
.